Kesiapan Implementasi Kelas Rawat Inap Standar di RSUD Sidoarjo Barat - Afif Kunaifi; Indasah Indasah; Agusta Dian Ellina; Andi Hayyun Abiddin (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Every individual has the right to obtain an equal standard of physical and mental health. The state is obliged to create quality health services and address health disparities caused by poverty, stigma, and discrimination. This study aims to analyze the readiness of the implementation of Standard Inpatient Classes at Sidoarjo Barat Regional Hospital. The research method in this study is qualitative with a case study approach. This study was conducted in March-April 2025. The data collection technique was with in-depth interviews with 30 informants. The informants in this study were several management ranks, Installation Coordinators, Midwives, and Nurses at Sidoarjo Barat Regional Hospital. The results of the study indicate that the West Sidoarjo Regional Hospital has met the minimum standards for facilities and infrastructure according to the 12 KRIS criteria. Funding for the implementation of KRIS at the West Sidoarjo Regional Hospital comes from the APBD (20%) and BLUD (80%) with consideration of budget flexibility, but requires additional health workers, especially nurses, to support the readiness of the implementation of KRIS, and strategic planning is needed regarding the policies implemented so as not to reduce the quality of hospital services, because the decline in the quality of service can reduce the interest of patient visits. In addition, the KRIS policy from the central government is still unclear and raises many questions, and the lack of socialization is feared to cause patient confusion, potentially reducing patient trust and visits to the West Sidoarjo Regional Hospital. Keywords: KRIS, BPJS, Readiness, Hospital, Facilities and Infrastructure.  ABSTRAK Setiap individu memiliki hak untuk mendapatkan standar kesehatan fisik dan mental yang setara. Negara berkewajiban menciptakan layanan kesehatan berkualitas serta mengatasi kesenjangan kesehatan yang disebabkan oleh kemiskinan, stigma, dan diskriminasi. Penelitian ini bertujuan untuk menganalisis kesiapan implementasi Kelas Rawat Inap Standar di RSUD Sidoarjo Barat. Metode penelitian dalam penelitian ini adalah kualitatif dengan pendekatan studi kasus. Penelitian ini dilakukan pada bulan Maret-April 2025. Teknik pengumpulan data  dengan indepth interview bersama 30 informan. Informan dalam penelitian ini merupakan beberapa jajaran manajemen, Koordinator Instalasi, Bidan, dan Perawat di RSUD Sidoarjo Barat. Hasil penelitian menunjukkan bahwa RSUD Sidoarjo Barat telah memenuhi standar minimal sarana dan prasarana sesuai 12 kriteria KRIS, Pendanaan implementasi KRIS di RSUD Sidoarjo Barat bersumber dari APBD (20%) dan BLUD (80%) dengan pertimbangan fleksibilitas anggaran, namun membutuhkan penambahan tenaga kesehatan, khususnya perawat, guna mendukung kesiapan implementasi KRIS, serta diperlukan perencanaan strategis mengenai kebijakan yang diterapkan agar tidak menurunkan mutu pelayanan rumah sakit, karena dengan menurunnya mutu pelayanan dapat mengurangi minat kunjungan pasien.Selain itu, kebijakan KRIS dari pemerintah pusat masih belum jelas dan menimbulkan banyak pertanyaan, serta kurangnya sosialisasi dikhawatirkan menyebabkan kebingungan pasien, berpotensi menurunkan kepercayaan dan kunjungan pasien ke RSUD Sidoarjo Barat. Kata Kunci: KRIS, BPJS, Kesiapan, Rumah Sakit, Sarana Prasarana.